Influence of Backscatter Radiation on Cranial Bone Fixation Devices. Issue 4 (June 2018) - Sakamoto, Yoshiaki; Koike, Naoyoshi; Takei, Hideyuki; Ohno, Mari; Shigematsu, Naoyuki; Kishi, Kazuo
Abstract : Abstract: Postoperative radiation can cause ulcer formation, leading to the denudation of skin over alloplastic materials. The influence of backscatter radiation from fixation devices has not been investigated. The aim of this study is to evaluate backscatter dose variations for different cranial bone fixation devices in an experimental model designed to simulate postoperative radiotherapy. The authors assessed the radiation backscatter doses associated with resorbable (PLLA-PGA) and titanium plates. The samples were irradiated with 6 and 10 MV photon beams from a linear accelerator. Measurements were obtained using an ionization chamber and radiochromic films cut from the same batch. As a result, the backscatter radiation of water and PLLA-PGA proportionally decreased as the depth increased. However, the backscatter radiation of the titanium plate increased just above the plate. This depth lies in the region of the scalp. Each material showed a dose of radioactivity that was higher at 10 MV than that at 6 MV. These devices showed a significant difference, which suggested that these materials amplified the dose compared with water at 6 MV. In conclusion, it is supposed that PLLA-PGA should be used to fix the cranium to decrease the potential for radiation ulcers.